2004
DOI: 10.1111/j.1440-1843.2004.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult pneumomediastinum in a SARS patient presenting as recurrent chest pain and acute ECG changes mimicking acute coronary syndrome

Abstract: Pneumomediastinum should be considered in SARS patients as a possible cause of chest pain and ECG changes that mimic acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
0
11
0
1
Order By: Relevance
“…Separately, Hasegawa et al[ 8 ] showed two children infected with the flu virus of H1N1 who developed SPM. Another elderly patient diagnosed with severe acute respiratory syndrome (SARS) presenting as recurrent chest pain and reversible electrocardiography changes was also found to develop pneumomediastinum though she had weaned from ventilatory support[ 9 ]. Autopsy results from COVID-19 patients commonly show bilateral, diffuse alveolar damage and interstitial mononuclear inflammatory infiltrates[ 10 ], suggesting the effect of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, Hasegawa et al[ 8 ] showed two children infected with the flu virus of H1N1 who developed SPM. Another elderly patient diagnosed with severe acute respiratory syndrome (SARS) presenting as recurrent chest pain and reversible electrocardiography changes was also found to develop pneumomediastinum though she had weaned from ventilatory support[ 9 ]. Autopsy results from COVID-19 patients commonly show bilateral, diffuse alveolar damage and interstitial mononuclear inflammatory infiltrates[ 10 ], suggesting the effect of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumomediastinum can present with T-wave inversion [3][4][5], electrical alternans [2], and low voltage [6]. These findings have been attributed to several mechanisms including cardiac rotation or displacement, right ventricular enlargement, and the insulation of the heart by mediastinal air [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…This condition has been associated with a variety of electrocardiographic (ECG) abnormalities including electrical alternans, T-wave inversion, loss of R wave progression, and low voltage QRS [2][3][4][5][6]. The following report describes a case of pneumomediastinum with apparent ST-segment elevation noted in the electrocardiogram that suggested acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Dans l'étude de Chu et al [6], incluant 123 patients ayant un SRAS, 13 d'entre eux (10,5 %) avaient un PMS. Au cours de cette pandémie, Tse et al [7] ont décrit un cas de PMS simulant un syndrome coronarien aigu chez une femme de 64 ans souffrant du SRAS.…”
Section: Cher éDiteurunclassified